Forest loss increases foliar insect and pathogen damage on poplar trees in natural riparian forests - Wang, Binli; Li, Ling (Frontiers in Plant Science, 2025)
Landscape-scale forest loss threats biodiversity and ecosystem functioning, but its effect on insect herbivory and pathogen infection on trees is not well understood. Little is known about how forest loss alters the effects of biotic and abiotic factors on foliar damages. Here, we assessed the relative importance of forest loss, microclimates, tree community attributes, leaf traits (e.g., specific leaf area, SLA), and arthropod abundance on insect and pathogen damage on laurel poplars in natural riparian forests in Xinjiang, China. We found that forest loss increased foliar insect herbivory directly through reduction of food availability and indirectly through reduction in tree diversity and host resistance (greater SLA). In comparison, forest loss only indirectly increased pathogen infection through lower tree diversity and associated higher SLA. Early season insect herbivory promoted later season pathogen infection. Microclimates were not associated with insect and pathogen damage, nor was arthropod abundance with insect herbivory. Our results suggest that forest loss reduced tree diversity which, in turn, changed host leaf traits and associational resistance and undermined bottom-up controls on insect herbivory and pathogen infection. Comparatively, top-down control of herbivory through predation was not significant. The positive relationship between tree diversity and host resistance (leaf traits, e.g., SLA) may be critical for maintaining forest health and ecosystem functioning in plantations and fragmented natural forests when insect pathogen damage at normal, non-outbreak conditions.